Phase composition and local environment of iron ions in gadolinium-doped iron oxide nanoparticles - Fedotova, Julia A.; Gumiennik, Uladzislaw E.; Vorobyova, Svetlana A.; Degtyarik Mikhail М.; Kharchanka, Andrei A.; Przewoznik, Janusz; Kapusta, Czeslaw (Journal of the Belarusian State University. Chemistry, 2022)
FeO ⋅ Fe2O3 ⋅ nH2O, Fe2.95Gd0.05O4 and Fe2.9Gd0.1O4 powders were obtained by chemical precipitation from aqueous solutions. The phase composition and local environment of iron ions in gadolinium-doped iron oxide nanoparticles were studied by X-ray diffraction analysis and nuclear gamma resonance (NGR) spectroscopy. Interpretation of radiographs and NGR spectra of synthesised samples indicates the presence of a superposition of maghemite γ-Fe2O3 and iron hydroxide α-FeOOH in the samples. It was found that under the deposition of powders in the presence of gadolinium nitrate, an increase in the content of iron hydroxide α-FeOOH is observed, which disappears after annealing at 200 °C.